Performance Analysis of a Savonius Wind Turbine in the Solar Integrated Rotor House - Manganhar, Abdul Latif; Rajpar, Altaf Hussain; Samo, Saleem Raza (Mehran University Research Journal of Engineering and Technology; Vol 36 No 3 (2017): July Issue, 2017)
Rooftop, building integrated and building augmented micro wind systems have the potential for small scale power generation in the built environment. Nevertheless, the expansion of micro wind technology is very slow and its market is strongly affected by the low efficiency of conventional wind generators. WAG-RH (Wind Accelerating and Guiding Rotor House) which is a new technique introduced to enhance the efficiency of vertical axis rotor. The present study utilizes other green energy element by integrating the WAG-RH with a solar heating system. In this effort roof of the WAG-RH has been utilized to heat air through micro solar chimney for creating buoyancy effect in the air flow channel at rotor zone in the WAG-RH. The integration is capable of improving the performance of rotor setup in the WAG-RH as well as providing hot air with sufficient air mass flow rate for space heating. The WAG-RH had brought about 138% increase in the performance coefficient(Cp) of conventional three bladed Savonius rotor, whereas solar integrated WAG-RH has contributed 162% increase in the Cp of the same rotor.